2016
DOI: 10.1002/cctc.201501239
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐single‐atom Platinum Induced by the Promoter Confined in Brucite‐like Lattice for Catalytic Reforming

Abstract: Pseudo-single atom Pt catalysts have achieved an excellent selectivity to branched paraffins and cycloalkanesi nn-hexaner eforming here. Highly dispersed platinum in single-atom and small clusters made up of severals eparated atoms wasp roduced under the inducemento fSno rZ ra sp romoting components. The Sn or Zr oxides were topologically transformed from layered double hydroxides as precursors, and thus homogeneouslyd ispersed owing to the confinemento ft he brucitelike lattices. The lattice confinementa lso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
1
28
0
1
Order By: Relevance
“…Therefore, it is reasonable to infer that metal atom clusters or single metal atoms are possibly formed on the surface of metal oxide nanosheets due to the low metal loading amount and the HT lattice confinement effect [10]. The EDS element-mapping images of PtInHT-FR further demonstrate the uniform distribution of Pt and In elements without aggregation, and support the probability of metal atoms or atom clusters type distributions [35]. Figure 3 shows SEM images of three series of samples.…”
Section: Phase Structure and Reconstruction Studymentioning
confidence: 80%
“…Therefore, it is reasonable to infer that metal atom clusters or single metal atoms are possibly formed on the surface of metal oxide nanosheets due to the low metal loading amount and the HT lattice confinement effect [10]. The EDS element-mapping images of PtInHT-FR further demonstrate the uniform distribution of Pt and In elements without aggregation, and support the probability of metal atoms or atom clusters type distributions [35]. Figure 3 shows SEM images of three series of samples.…”
Section: Phase Structure and Reconstruction Studymentioning
confidence: 80%
“…MMOs have been frequently used as supports for heterogeneous catalysts . Recent studies have shown that the acidity and basicity of MMO supports can be controlled by tuning the composition of the brucite‐like host layers in the LDH precursor.…”
Section: Mmo Based Nanocatalystsmentioning
confidence: 99%
“…Further analysis revealed that the porphyrinic Fe‐N 4 moiety can facilitate the breakage of OO bond and thus lowers the reaction energy barrier, leading to the excellent activity for oxygen reduction reaction (ORR) . Transition metal dopants were also reported to trap isolated Pt atoms by Ma et al The authors found that the Sn or Zr dopants can be confined in the brucite‐like lattice of layered double hydroxide, affording electron‐rich Sn or electron‐defected Zr sites on the surface, thereby providing strong binding sites for anchoring isolated Pt atoms . In addition, some specific additives, such as alkali metals, can stabilize isolated metal atoms on supports by enhancing the metal–support interaction.…”
Section: Synthesis Strategies For Single Metal Atom Catalystsmentioning
confidence: 99%